The Immigrant World of Ybor City: Italians and Their Latin Neighbors in Tampa, 1880-1980 - Iacovetta, Franca (Labour / Le Travail, 1989)
The article reviews the book, "The Immigrant World of Ybor City: Italians and Their Latin Neighbors in Tampa, 1880-1980," by Gary R. Mormino and George E. Pozzetta.
Keywords: IMMIGRANT World of Ybor City: Italians & Their Latin Neighbors in Tampa 1880-1980 (Book); Immigrants; MORMINO, Gary R.; Nonfiction; POZZETTA, George E.; REVIEWS; books

Family Life in Central Italy, 1880-1910: Sharecropping, Wage Labor and Coresidence - Iacovetta, Franca (Labour / Le Travail, 1987)
This article reviews the book, "Family Life in Central Italy, 1880-1910: Sharecropping, Wage Labor and Coresidence," by David I. Kertzer.
Keywords: FAMILY Life in Central Italy: 1880-1910: Sharecropping, Wage Labor & Coresidence (Book); KERTZER, David I., 1948-; Nonfiction; REVIEWS; SHARECROPPERS; books